2018
DOI: 10.1186/s13072-018-0195-z
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of regulatory elements during erythro-megakaryopoiesis identifies hematopoietic lineage-commitment points

Abstract: BackgroundEnhancers and promoters are cis-acting regulatory elements associated with lineage-specific gene expression. Previous studies showed that different categories of active regulatory elements are in regions of open chromatin, and each category is associated with a specific subset of post-translationally marked histones. These regulatory elements are systematically activated and repressed to promote commitment of hematopoietic stem cells along separate differentiation paths, including the closely related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 58 publications
(61 reference statements)
7
39
0
1
Order By: Relevance
“…While this reduction in numbers of active genes and regulatory elements appears to occur in most lineages of blood cells, it was not observed in megakaryocytic cells, which retain aspects of the regulatory landscape and transcriptomes of multilineage progenitor cells. Similarity of MK to multilineage progenitor cells has been discerned previously from phenotypic similarities (Huang and Cantor 2009), transcriptome data (Sanjuan-Pla et al 2013;Psaila et al 2016), and global epigenetic profiles (Heuston et al 2018). Recent studies have shown that MK cells can be derived from multiple stages of progenitor cells, including HSC, CMP, and MEP (Sanjuan-Pla et al 2013;Psaila et al 2016).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…While this reduction in numbers of active genes and regulatory elements appears to occur in most lineages of blood cells, it was not observed in megakaryocytic cells, which retain aspects of the regulatory landscape and transcriptomes of multilineage progenitor cells. Similarity of MK to multilineage progenitor cells has been discerned previously from phenotypic similarities (Huang and Cantor 2009), transcriptome data (Sanjuan-Pla et al 2013;Psaila et al 2016), and global epigenetic profiles (Heuston et al 2018). Recent studies have shown that MK cells can be derived from multiple stages of progenitor cells, including HSC, CMP, and MEP (Sanjuan-Pla et al 2013;Psaila et al 2016).…”
mentioning
confidence: 83%
“…Detailed information about the cell populations and cell lines analyzed is in Supplemental Material, section 1. The ChIP-seq and ATAC-seq procedures followed previously published methods (Wilson et al 2010;Buenrostro et al 2013;Wu et al 2014;Heuston et al 2018).…”
Section: Cell Populations and Sources Of Epigenomic And Transcriptomimentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, the amount of information about gene expression levels and epigenetic regulatory landscapes in mammalian hematopoietic cells has increased exponentially, both through the work of individual laboratories [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] as well as the work of major consortia such as ENCODE and Blueprint. These data currently are provided in differing formats from diverse resources, with no common data processing or analysis, for example, to find significant peaks of signals.…”
Section: Compile and Determine Epigenetic Features And Transcript Lmentioning
confidence: 99%
“…ATAC-Seq ATAC-seq was performed as previously described 39 . Briefly, 5 x 10 4 sorted proerythroblasts were lysed by gently pipetting in cold lysis buffer.…”
Section: Chip-seq Analysismentioning
confidence: 99%